Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Efektivitas Pendidikan di Sekolah Dasar: Kajian Pustaka - Hafifa, Izatul; Wahyuni, Dinda; Desyolina, Halfi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The leadership of school principals plays a crucial role in enhancing the effectiveness of education in primary schools. This study aims to analyze the contribution of school leadership to educational quality through learning leadership, transformational leadership, and teacher competency development approaches. Furthermore, the study also discusses the implementation of educational policies and work discipline management within the school environment. The findings indicate that effective principals, as instructional leaders, managers, and change agents, can improve teaching quality, student motivation, and parental involvement in education. Through visionary and adaptive leadership, principals can create an innovative learning environment that focuses on student development. Therefore, strengthening the leadership capacity of school principals is key to improving the quality of primary education.